Youth In South Africa : (in)visibility and national development - Brooks, Heidi; Langa, Malose; De Lannoy, Ariane (Book collections on Project MUSE., 2021)
"South Africa is characterised by a youthful population, and the challenges and possibilities that characterise the young generation are both warning signs and beacons of hope for a nation founded on social justice. Youth in South Africa: Agency, (in)visibility and national development takes stock of the nation's development as it affects young people. Authors offer both personal and professional insights into the ways in which the youth navigate their own pathways to adulthood. These include formal and informal engagements with politics, as well as protest, (un)employment, entrepreneurship, education, religion, experiences with sexuality and violence and a multitude of other life experiences. Contributors paint a picture of the initiative, agency and resilience of the youth, as well as the challenges before them. Authors also identify the state of "waithood" faced by those unable to make the transition out of youth into full adulthood as a result of their socio-economic circumstances and political context. By engaging these experiences and insights, and primarily informed by the inputs of young people, the authors highlight the limitations of existing youth policies."--